Rancang Bangun Alat Penyortir Beras Dengan Sistem Penggerak Motor Listrik - Teguh Catur Prambudi; Laily Ulfiyah; Lukman Hadiwijaya (Indonesian Society of Applied Science, 2021)
Rice is the staple food most consumed by Indonesians which is produced from milling dry unhusked rice grain. In the dry unhusked rice grain milling process, rice has different forms, namely whole and cracked rice. This is due to the poor quality of the paddy rice. The different in forms has led to a different selling value. Whole rice is more expensive than the other. Therefore, sorting was done to obtain the differences. This study was carried out to build rice sorting device with a system in the form of a launch crank mechanism as a vibration system. This device has several components consisting of two mesh and two turnbuckle eye & eye as the sieve tilt adjustment. In the tilt experiment, two variations of the angle were obtained, namely an angle of 10° and an angle of 15°. This device uses a single-phase electric motor as the driving force of the launching crankshaft. The transmission system uses a pulley and a v-belt from a single-phase electric motor that is passed to the pulley. From the test results that have been carried out two-angle variations with a capacity of 10 kg. At an angle of 15°, 69% pure rice is obtained with less optimal results because the slope of the angle is too steep. Whereas at an angle of 10°, the yield of pure rice is 85% which has a less angular slope so that the sorting of rice is maximized.